HUBUNGAN INDEKS MASSA TUBUH DENGAN RISIKO DIABETES MELLITUS TIPE 2 - Yuni Kurniawaty (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Diabetes Mellitus (DM) is a metabolic disease currently a global health problem. A higher waist circumference and higher body mass index (BMI) are associated with an increased risk of type 2 diabetes, although the association may vary in different populations. Objective: Research shows that there is a significant positive correlation of body fat percentage with the incidence of diabetes. The aim of the study was to identify the relationship of BMI with the risk of developing Type 2 DM in the elderly. Methods: The research design used was observational with cross sectional approach. The population in this study 40-90 years old at RW 5 Sawunggaling Surabaya who did not have a history of T2DM. Sampling technique was simple random sampling, where 80 samples. Independent variable is eldery BMI. Dependent variable is risk for elderly T2DM. Results: Spearman Rank statistical test results p = 0.032 significantly states there is a relationship between BMI and risk of T2DM correlation coefficient values ​​or the level of relationship + 0.240. There is a relationship of BMI with the risk of T2DM in the elderly. Conclusion: The higher the value of BMI, the more risk an elderly person has T2DM. It would be better if the elderly keep their body remains ideal so as to reduce the risk of T2DM. The right way for the elderly to maintain an ideal body is a challenge in further.